Annual report of the IICA office in Trinidad and Tobago for 1985 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
This document is an annual report of the IICA Office in Trinidad and Tobago for the year of 1985. It contains anual achievements, historic entities cooperation, synthesis of the actions of technical cooperation, also a list of published documents by the Unit during the year.